2007
DOI: 10.12693/aphyspola.111.141
|View full text |Cite
|
Sign up to set email alerts
|

Electroresistance of Electrically Nonhomogeneous La0.67Ca0.33MnO3/MgO Thin Films

Abstract: Current and electrical field-induced electroresistive effects were investigated for La 0.67 Ca 0.33 MnO 3 /MgO thin films demonstrating nanosized electrical inhomogeneities. Two different models based on enhanced conductivity of intergrain boundaries by injecting spin-polarized carriers from ferromagnetic grains and electrical field-enhanced hopping of carriers in high resistance intergrain media were carried out to explain nonlinear electrical properties of the films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This is due to 9 % mismatch of lattice constants of a pseudo cubic single phased La 0.67 Ca 0.33 MnO 3 and MgO (100) face. The surface of the cleaved substrates was investigated by atomic force microscopy [2]. Terracelike structures with a step height typically from 5 nm to 25 nm were revealed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to 9 % mismatch of lattice constants of a pseudo cubic single phased La 0.67 Ca 0.33 MnO 3 and MgO (100) face. The surface of the cleaved substrates was investigated by atomic force microscopy [2]. Terracelike structures with a step height typically from 5 nm to 25 nm were revealed.…”
Section: Methodsmentioning
confidence: 99%
“…Significant place amongst novel materials belongs to materials with properties modified at nanostructural and mesoscopic levels by fast intensive energy influence. That influence could be realized by power laser illumination [1], high voltage electric pulses [2] and shock waves [3].…”
Section: Introduction *mentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray diffraction measurements demonstrated that so prepared films were single-phased and of pseudocubic perovskite structure and that the films on MgO (100) substrate were polycrystalline. Large dc resistance show polycrystalline character of the used films [1,5,6], too. The film surface was examined by atomic force microscope.…”
Section: Experimental Investigations and Theoretical Modelmentioning
confidence: 96%
“…The film deposition procedure and investigation of the properties of the electrically nonhomogeneous films were described in Ref. [4]. The prepared films demonstrated the PM-FM transition in the temperature range 125-140 K. A pair of Ag pads (width w = 1 mm and the gap between them d = 10 ÷ 30 µm) magnetron sputtered onto the film surface through a mask served as electrodes for electrical measurements.…”
Section: Preparation Of High Resistive Samples and Experimental Setupmentioning
confidence: 99%